THE INFLUENCE OF THE CASTRATION METHOD AND THE WEIGHT BEFORE SLAUGHTER ON THE INDICATORS OF THE MEAT CUTS OF PIG CARCASSES - Oleksandr MYKHALKO; Mykola POVOD; Bogdan GUTYJ; Michael HYLL; Tetyana VERBELCHUK; Serhii VERBELCHUK; Serhii LUHOVYI; Victor SHUPLYK; Yurii KOVALCHUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of the article was to investigate the dependence of the slaughter characteristics of boars and the method of their castration on the weight before slaughter. To carry out the experiment, 30 surgically and 30 immunocastrated male pigs weighing 100, 110 and 120 kg were taken and reared under the same conditions in an industrial pig complex. After completion, the pigs were slaughtered and the carcasses were cut into cuts. The weight and content of the cuts were examined separately in the shoulder-scapular third, back-loin third and pelvis-femoral third of all groups of experimental pigs. According to the experimental results, the influence of the castration method on the weight and content of meat cuts, bacon pieces and bones in the shoulder-scapular third was found to be in favour of the immunocastrated boars. The weight and content of meat pieces in the posterior lumbar third were the same in surgically and immunocastrated boars, with the exception of bones. Meat pieces, bacon and bones in the pelvic femoral third of the pelvis did not differ between surgically and immunocastrated male pigs. Increasing the weight before slaughter from 100 to 120 kg had a positive effect on the weight and meat piece content of the piglets in both castration methods.